Thermal stability of Au–TiO2 nanocomposite films prepared by direct liquid injection CVD. (December 2015) - Avril, L.; Bourgeois, S.; Marco de Lucas, M.C.; Domenichini, B.; Simon, P.; Addou, F.; Boudon, J.; Potin, V.; Imhoff, L.
Abstract: Nanocomposite films composed of gold nanoparticles (AuNPs) embedded in a TiO2 matrix have been prepared by direct liquid injection chemical vapor deposition process, using preformed nanoparticles and titanium isopropoxide as precursors. The spherical AuNPs about 4.1 nm in diameter were synthesized by using gold (III) chloride trihydrate and stabilized by thiol ligands. The depositions were carried out by performing at first oxide deposition, then gold nanoparticle one and capping with oxide. The morphology, structure; the chemical state and optical properties of nanocomposite films were characterized by scanning electron microscopy, Raman, X-ray photoelectron and UV–Vis absorption spectroscopies, respectively. The stability of the films upon thermal annealing up to 800 °C was studied. Highlights: Preformed gold nanoparticles and titanium tetraisopropoxide were used as precursors. Au–TiO2 films were composed of gold nanoparticles embedded in the TiO2 matrix. The growth of TiO2 films was not modified by the insertion of gold nanoparticles. The size of the preformed gold nanoparticles was preserved during the deposition. The annealing treatments did not modify the morphology of the gold nanoparticles.